Rolnictwo Europy Środkowo-Wschodniej w okresie transformacji ustrojowej gospodarki - Grykień, Stanisław (Agriculture of Middle Eastern Europe During a Period of Economic Transformation, 2005)
Privatization in rural Middle Eastern Europe is an important factor in the general political and economic transition in this part of Europe. Agriculture was always a significant component in development strategies of the former socialist countries. After the fall of the communist system it became an important factor in the struggle for political influence.Models in transformation in agriculture were different in countries situated in the region. These dissimilarities were the result of the socio-economic and political situation in which these particular countries were found at the time. After World War II agriculture in Middle and East European countries was created by economic policy dependent on the Soviet Union. As a result until the beginning of 1990 in their national economies dominated public property of means of production.Key issues of agricultural transformation in Middle Eastern Europe are: privatisation of land and assets; satisfaction a request of former farmers and their heirs whose land had been collectivised; restructuring of large-scale farms; implementation of market economy; development of individual farming (peasant farms); increase of efficiency of agriculture.Restructuring is both a political, economic and social process. Restructuring is political in that land privatization and farm restructuring are highly dependent on local politics, and continued debates about the strategy and the implementation of the reforms. It is economic, in that restructuring must ensure the optimal organisation of farm.The process of transformation in agriculture in Middle Eastern Europe was imposed by historic necessity resulting from the failure of communist ideology. It can already be confirmed that the heritage of the communist period left behind it. It is visible as the attachment to collective property, the lack of individual initiative connected with mental barriers, the power of informal connections and pro-socialist feelings among a large proportion of the rural population.The period of a centrally planned economy caused common consequences in mentioned countries. There are among other things mental problems and spatial structure of plots. Workers from different kinds of state farms were not interested in establishing their private farms. They were used to working eight hours per day as workers in factories do and a typical link between farmer and soil was snap. Another remains in geographical space where big plots of fields typical for state farms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 115-127